Process, optimization, and characterization of budesonide-loaded nanostructured lipid carriers for the treatment of inflammatory bowel disease. (3rd July 2018) - Sinhmar, Gurpreet Kaur; Shah, Neel N.; Chokshi, Nimitt V.; Khatri, Hiren N.; Patel, Mayur M.
Abstract: The major challenge involved in the treatment of inflammatory bowel disease is targeted delivery of the drug at the site of inflammation. As nanoparticles possess the ability to accumulate at the site of inflammation, present investigation aims at development of Budesonide-loaded nanostructured lipid carrier systems (BDS-NLCs) for the treatment of inflammatory bowel disease. BDS-NLCs were prepared by employing a high pressure homogenization technique. Various preliminary trials were performed for optimization of the NLCs in which different processes, as well as formulation parameters, were studied. The BDS-NLCs was optimized statistically by applying a 3-factor/3-level Box–Behnken design. Drug concentration, surfactant concentration, and emulsifier concentration were selected as independent variables, and % entrapment efficiency and particle size were selected as dependent variables. The best batch comprises of 10%, 7%, and 20% w/w concentration of drug, surfactant, and emulsifier, respectively, with % entrapment efficiency of 92.66 ± 3.42% and particle size of 284.0 ± 4.53 nm. Further, in order to achieve effective delivery of nanoparticulate system to colonic region, the developed BDS-NLCs were encapsulated in Eudragit ® S100-coated pellets. The drug release studies of pellets depict intactness of BDS-NLCs during palletization process, with f2 value of 75.879. The in vitro evaluation of enteric-coated pellets revealed that a coating level of 15% weight gain is needed in order to impart lag time of 5 h (transit time to reach colon). The results of the study demonstrate that the developed BDS-NLCs could be used as a promising tool for the treatment of inflammatory bowel disease.